Unaccompanied & Denied: Regional Legal Framework for Unaccompanied Minors Asylum Seekers (UMAS) - Nordin, Rohaida; Whelan, Jennifer; Aziz, Saidatul Nadia Abd.; Rajagopal, Meerah Deiwi (UI Scholars Hub, 2015)
Unaccompanied minor asylum seekers are vulnerable and thus, provided special international law protections. However, in reality, they are being mistreated as illegal immigrants and on the receiving end of ethnic violence, discrimination, restrictions in enjoyment of their rights duly recognised by international human rights law. This article identifies legislative, policy and support mechanisms which encompass the minimum UMAS guardianship standards at international law and which are evidence-based from best practice models for the provision of guardians for UMAS internationally. It presents situation of UMAS in relation to human rights violations with emphasis on the legal framework and practices in Australia and five ASEAN State Members. This article also highlights the various stands taken by various countries providing better legal framework and practices regarding the terms for protection and enforcement of human rights for UMAS. Finally, this article provides recommendations for Australia and ASEAN Member States to adopt in order to realise the international human rights of UMAS with respect to guardianship.